Effect of Cosmos caudatus (Ulam raja) supplementation in patients with type 2 diabetes: study protocol for a randomized controlled trial - Cheng, Shi Hui; Ismail, Amin; Anthony, Joseph; Ooi, Chuan Ng; Abdul Hamid, Azizah; Mohd Yusof, Barakatun Nisak (BioMed Central, 2016)
BACKGROUND: Type 2 diabetes mellitus is a major health threat worldwide. Cosmos caudatus is one of the medicinal plants used to treat type 2 diabetes. Therefore, this study aims to determine the effectiveness and safety of C. caudatus in patients with type 2 diabetes. Metabolomic approach will be carried out to compare the metabolite profiles between C. Caudatus treated diabetic patients and diabetic controls.